2006
DOI: 10.1029/2005jd006840
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the effect of a Saharan dust storm on oxygenated organic compounds at Izaña, Tenerife (July–August 2002)

Abstract: [1] In July-August 2002 the field measurement campaign Mineral Dust and Tropospheric Chemistry (MINATROC) was carried out at the Global Atmosphere Watch station at Izaña, Tenerife, to study the interaction of mineral dust aerosol and tropospheric chemistry. Organic trace gas mixing ratios were determined for the following: alkanes (e.g., propane); alkenes (isoprene); aromatic compounds (toluene); and oxygenated species (CO, methanol, formaldehyde, acetaldehyde, and acetone) simultaneously with aerosol measurem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 61 publications
2
10
0
Order By: Relevance
“…Analogous FT concentrations of 2-methylthreitol and 2-methylerythritol were measured in the present study under the SAL (7.3 and 16.8 ng m −3 ; Table 2) and over the central China FT (8 and 17 ng m −3 ; Fu et al, 2014), one of the most important source regions of isoprene emission in the world during summertime (Guenther et al, 1995). Similar SOA ISO concentrations were found in the BL within the SAL and the WES (∼ 17 and ∼ 16 ng m −3 respectively) revealing the emission and subsequent ascending transport of biogenic or anthropogenic compounds, as found in previous studies performed at Izaña, which observed emissions of isoprene during daytime associated with anthropogenic compounds (Salisbury et al, 2006). A statistically significant correlation among 2-MT1 and 2-MT2 was found for individual values (r = 0.90, p < 0.01) as previously observed in other studies (Ion et al, 2005;El Haddad et al, 2011), but with a mass concentration ratio of 2-MT1 vs. 2-MT2 (slope from linear regression = 2.3) slightly lower than that found by El Haddad et al (2011).…”
Section: Tracers Of Isoprene Oxidation (Soa Iso)supporting
confidence: 67%
“…Analogous FT concentrations of 2-methylthreitol and 2-methylerythritol were measured in the present study under the SAL (7.3 and 16.8 ng m −3 ; Table 2) and over the central China FT (8 and 17 ng m −3 ; Fu et al, 2014), one of the most important source regions of isoprene emission in the world during summertime (Guenther et al, 1995). Similar SOA ISO concentrations were found in the BL within the SAL and the WES (∼ 17 and ∼ 16 ng m −3 respectively) revealing the emission and subsequent ascending transport of biogenic or anthropogenic compounds, as found in previous studies performed at Izaña, which observed emissions of isoprene during daytime associated with anthropogenic compounds (Salisbury et al, 2006). A statistically significant correlation among 2-MT1 and 2-MT2 was found for individual values (r = 0.90, p < 0.01) as previously observed in other studies (Ion et al, 2005;El Haddad et al, 2011), but with a mass concentration ratio of 2-MT1 vs. 2-MT2 (slope from linear regression = 2.3) slightly lower than that found by El Haddad et al (2011).…”
Section: Tracers Of Isoprene Oxidation (Soa Iso)supporting
confidence: 67%
“…The abundant fine dust particulates would be conductive to those heterogeneous reactions occurring on their large surface in the troposphere (Jacob, 2000;Andreae and Crutzen, 1997). It was proved that alkene, olefinic and aliphatic compounds could be oxidized to formaldehyde and acetaldehyde through the heterogeneous reactions (Thomas et al, 2001;Salisbury et al, 2006). Therefore, the contribution from heterogeneous reactions to the two species cannot be ruled out in this study.…”
Section: Influences Of Dust Storm On Atmospheric Carbonylsmentioning
confidence: 81%
“…Mineral dust is transported from North Africa along three pathways: westward across the Atlantic to the Americas, northward across the eastern Mediterranean to Europe, and eastward across the eastern Mediterranean to the Middle East and Asia (Middleton and Goudie 2001). Saharan dust events have often been observed at IZO (Alastuey et al 2005;Arimoto et al 1995;Díaz et al 2006;Kandler et al 2007;Maring et al 2000;Rodríguez et al 2011;Salisbury et al 2006;Schmitt and Volz-Thomas 1997;Smirnov et al 1998), CMN (Bonasoni et al 1997(Bonasoni et al , 2004Cristofanelli and Bonason 2009;Cristofanelli et al 2009b;de Reus et al 2005;Gobbi et al 2003;Marenco et al 2006;Putaud et al 2004;Van Dingenen et al 2005), and JFJ (Chou et al 2011;Collaud Coen et al 2004;Cozic et al 2008;Fierz-Schmidhauser et al 2010;Nyeki et al 1998b;Schwikowski et al 1995;Zieger et al 2012). Furthermore, long-range transport of Saharan dust over a pathway spanning from Asia and the Pacific to western North America has been identified at WHI by McKendry et al (2007).…”
Section: Dust and Volcanic Emissionsmentioning
confidence: 99%
“…The model simulated a decrease in global tropospheric O 3 mass by~5 % due to heterogeneous reactions, and implied that the most important heterogeneous reaction was the uptake of HNO 3 on the dust surface. Salisbury et al (2006) observed the concentrations of the organic compounds CO, CH 3 OH, formaldehyde (HCHO), acetaldehyde (CH 3 CHO), C 3 H 6 O, C 3 H 8 , C 5 H 8 , and toluene (C 6 H 5 CH 3 ) under both normal conditions and during large dust storms, in order to investigate the effects of mineral dust on oxygenated organic species. However, no clear production for CH 3 CHO or HCHO on dust particles was ascertained.…”
Section: Dust and Volcanic Emissionsmentioning
confidence: 99%
See 1 more Smart Citation